Evaluation of moisture susceptibility of asphalt mixture using liquid anti-stripping agents. (30th July 2017) - Park, Dae-Wook; Seo, Woo-Jin; Kim, Jun; Vo, Hai Viet
Highlights: Asphalt mixtures containing anti-stripping additives were evaluated. Several tests were conducted to qualify mixtures' moisture susceptibility. Hamburg wheel tracking test data were analyzed by several methodologies. The result shows that the developed agents enhance moisture resistance and rutting resistance. Field testing indicates the feasibility of applying the anti-stripping agent. Abstract: In this study, aliphatic amine type-developed liquid anti-stripping agents, were evaluated for application in asphalt mixture. Boiling water test was conducted as a screening test, followed by indirect tensile test. The tensile strength ratio and image analysis method were used to evaluate the moisture susceptibility of the asphalt mixtures. In continuation of Hamburg wheel tracking test to evaluate the rutting resistance of the asphalt mixture, actual field application was performed. The results showed that the developed agents improved the stripping and rutting resistance of the asphalt mixture compared to those of the one containing other anti-stripping additives.